Alcívar Sánchez,Bella Melany(2023)EVALUACIÓN SENSOMÉTRICA Y CROMÁTICA DE UN LICOR ESPIRITUOSO INCORPORANDO ZUMO DE CAÑA DE AZÚCAR (Saccharum officinarum) Y PANELA EN EL PROCESO DE TRIDESTILACIÓN.Quevedo.UTEQ.118p. - Alcívar Sánchez , Bella Melany (2023)
Spirits have been commonly consumed by ancestral cultures, currently these liquors are being produced and modified in an artisanal way by small producers who cultivate sugar cane. The objective of this research is to evaluate the effect on the sensometry and chromatic characteristics of a spirituous liquor incorporating sugar cane juice (Saccharum officinarum) and panela in the tridistillation process. The research was carried out in the laboratories of unitary operations and the bromatology laboratory belonging to the Quevedo State Technical University "La María" campus. For the process of this research, a Completely Randomized Research Design (DCA) – 2 was used, with a trifactorial arrangement of AxBxC presenting 8 treatments with 3 repetitions, thus obtaining 24 experimental units. Factor A was the concentration of panela, factor B the dose of sugarcane juice and factor C the °GL of the liquor. The data or experimental responses were subjected to a normality test which led to the use of a non-parametric test such as that of Freedman and Holm. The statistical analysis of chromaticity showed no significant difference and to define its indicators of brightness, chroma and hue, based on the statistical analysis of sensometry, the spirituous liquor presented a brightness (L) of 97.49; chroma 22.8866 and hue -28.0274, which corresponds to a medium bluish, slightly violet color shade. Treatment 5, symbolized by a1b0c0 (5% panela, 3.5% cane juice, 35° GL) had the best characteristics with attributes of medium bluish color, fruity mandarin odor, mild sweet flavor, balanced liquor impression and acceptability that pleased the panelists. In addition, viscosity was determined at a value of 0.0581 centipoise at 25°C.